Efficacy of Teach Project on the Mathematical Problem-Solving Proficiency of First-Year Criminology Students - Ubaldo, Glenn Jhubert (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the efficacy of the T.E.A.C.H. Project—Think, Explore, Apply, Calculate, and Hone—in improving the mathematical problem-solving proficiency of first-year Bachelor of Science in Criminology students enrolled in Mathematics in the Modern World. Anchored in Polya’s Four-Step Problem-Solving Model and organized through an Input–Process–Output framework, the study employed a quantitative, quasi-experimental pre-test–post-test design. The respondents were 51 students from two intact classes selected through purposive sampling, with 26 assigned to the experimental group and 25 to the control group. A validated and reliability-tested researcher-made mathematical problem-solving test was administered before and after the two-month intervention. Data were analyzed using frequency, percentage, mean, standard deviation, weighted mean, paired- and independent-samples t-tests, chi-square, and Spearman Rank-Order correlation. Both groups demonstrated significant improvement, but the experimental group achieved a higher post-test mean of 43.769 than the control group’s 38.320, with a p-value of 0.000. Moreover, 80.8% of the experimental group attained an Excellent rating compared with 52% of the control group. The intervention positively influenced students’ ability to understand problems, devise plans, carry out solutions, and look back at their answers. Gender was significantly related to problem-solving performance, whereas age, class section, and academic standing were not. Persistent difficulties involved measures of central tendency, mathematical reasoning, and complex tasks requiring analysis, evaluation, application, and synthesis. The study concluded that the T.E.A.C.H. Project is an effective structured instructional intervention, although the initial difference between the groups limits purely causal interpretation. Its continued integration into mathematics instruction, supported by teacher training, differentiated assistance, and targeted enrichment activities, was recommended. The study supports SDG 4: Quality Education by strengthening mathematical competence, critical thinking, and learner engagement. It contributes to educational and institutional sustainability by providing an evidence-based approach for addressing recurring learning gaps and improving mathematics instruction.
Keywords: Mathematics In The Modern World; Mathematical Problem-Solving Proficiency; Polya’s Four-Step Problem-Solving Model; Quality Education; T.E.A.C.H. Project; Traditional Instruction